Historical blocking: TZ 2020-10-27 to 2020-10-28 (Tanzania) - Voidly (Voidly Global Censorship Index, 2020)
CRITICAL severity censorship detected in Tanzania. Data sourced from ooni-historical-backfill.
Censorship Incident ID: TZ-2020-0005. Severity: critical. Confidence: 89%